Excitation of the n=2 levels of hydrogen by proton impact for hydrogen beam diagnostics. (15th January 2015) - Schultz, D R; Ovchinnikov, S Y
Abstract: The atomic orbital close coupling approach has been used to compute a comprehensive data set for proton-impact excitation of atomic hydrogen owing to the need for complete data for motional Stark effect spectroscopy of fusion plasmas enabled by neutral beam injection.